2022
DOI: 10.1128/spectrum.01029-22
|View full text |Cite
|
Sign up to set email alerts
|

Pan-Genome Analysis of Campylobacter: Insights on the Genomic Diversity and Virulence Profile

Abstract: Pathogenic members of the genus Campylobacter are recognized as one of the major causative agents of human bacterial gastroenteritis. This study revealed the pan-genome of 39 Campylobacter species, provided the most updated reconstruction of the global virulence gene pool of 39 Campylobacter species, and identified species-related virulence differences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 65 publications
2
7
0
Order By: Relevance
“…Using the Campylobacter genus core genome, we derived a core genome phylogeny for classifying Campylobacter isolates. The delineation of species on the core genome phylogenetic tree is consistent in many instances with previous studies, as closely related Campylobacter species in established groups can be found within the same major clades of the phylogenetic tree ( 13 , 14 , 40 , 43 , 49 51 ). With the rapid expansion of the Campylobacter genomes and additional diversity from new genomes sequenced, it is inevitable that new Campylobacter genomes may not be assignable to an established species or may be inconsistent with traditional species.…”
Section: Discussionsupporting
confidence: 88%
“…Using the Campylobacter genus core genome, we derived a core genome phylogeny for classifying Campylobacter isolates. The delineation of species on the core genome phylogenetic tree is consistent in many instances with previous studies, as closely related Campylobacter species in established groups can be found within the same major clades of the phylogenetic tree ( 13 , 14 , 40 , 43 , 49 51 ). With the rapid expansion of the Campylobacter genomes and additional diversity from new genomes sequenced, it is inevitable that new Campylobacter genomes may not be assignable to an established species or may be inconsistent with traditional species.…”
Section: Discussionsupporting
confidence: 88%
“…Previous attempts to delete htrB in C. jejuni have failed, further supporting its essentiality [ 76 ]. Zhong et al interestingly highlighted the gene htrB as a core virulence gene across 39 representative Campylobacter species [ 77 ]. The other core virulence genes that they found were porA, PEB4, cheY, Cj1135 and kspF.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, htrB and PEB4 which have been found to be core virulence genes across Campylobacter spp. are essential and therefore would warrant further investigation [ 77 ]. The core essential gene list produced indicates that there are many essential genes that are critical to the fitness and/or survival of Campylobacter but have a hypothetical/unknown function.…”
Section: Discussionmentioning
confidence: 99%
“…play a crucial role in advancing our knowledge of the dynamics and characteristics of circulating lineage clusters. A high genetic diversity of C. jejuni strains has been extensively documented worldwide and possesses a notable capacity for genetic exchange, enhancing its adaptability ( Golz et al, 2020 ; Bravo et al, 2021 ; Harrison et al, 2021 ; Ocejo et al, 2021 ; Prendergast et al, 2022 ; Zhong et al, 2022 ; Hull et al, 2023 ). Notably, extensive introgression (transfer of genetic material between different species), predominantly from C. jejuni to C. coli, has been observed, resulting in the replacement of approximately 10 and 23% of the C. coli core genome with C. jejuni DNA in ST-828 and ST-1150 CCs, respectively ( Sheppard et al, 2008 ; Tanoeiro et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study on the genomic diversity and virulence profile of the genus Campylobacter demonstrated that the number of genes has undergone expansion or contraction during the evolution of different Campylobacter species ( Zhong et al, 2022 ). VFDB analysis revealed that many strains (75 out of 131) carried virulence genes associated with bacterial species other than Campylobacter spp., suggesting potential gene transfer events between different bacterial species.…”
Section: Discussionmentioning
confidence: 99%